The emergence of a medical exception from patentability in the 20th century - Piper, S; Stamatia Piper (2008)
Many patent law dilemmas arise from a failure to understand technologies as embedded in broader social, economic and political realities and to contextually analyze these legal phenomena. This narrowness leads to poor legal development, of which the modern medical exception from patentability is one example. Judges have difficulty interpreting it, patentees do not understand its purpose and it does not protect the important medical technologies to which the public would like access. This thesis applies a legal pluralist analysis to examine the emergence of the medical methods exception in order to understand why it was created and legislated. It starts by examining the origins of the exception in the caselaw, and the informal, concurrent norm established by the emerging medical profession in the early 20th century. It then proceeds to examine why the medical profession might have sought and enforced a norm prohibiting its members from patenting, and concludes that this arose from the need of the medical profession to distance itself from the patent law. As a result, professionalizing physicians established an internal normative order that mimicked and in many cases replaced the effect of the formal law. The thesis then proceeds to examine how the form of the informal norm evolved in the period between WWI and WWII, finding that the profession’s norm transformed and broke down concurrently with its efforts to achieve external legitimacy through legislation. That breakdown arose from factors which included growing labour mobility, greater understanding of the benefits of patents, and a growing role of science and industry in medicine that threatened the profession’s access to valuable medical innovation. The thesis concludes with a study of a current case (Myriad Genetics) that applies the thesis’ theoretical framework to a present dispute over the role the law should play in regulating genetic diagnostic tests.